2008
DOI: 10.1097/prs.0b013e31817d60e0
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Tissue Coverage and Outcome of Gustilo Grade IIIB Midshaft Tibia Fractures: A 15-Year Experience

Abstract: Soft-tissue coverage is not the only determinant for successful outcome. Delayed coverage resulted in higher nonunion rates. Despite high nonunion rates, 89 percent of fractures ultimately healed successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Flap (IIIB) Pro [11] Vascular injury Pro [7] Open injury Pro [2,5] Weightbearing status postoperatively Pro [15,26] Con [35] Fibular fracture fixation Pro [15,38] Con [39,42] …”
Section: Bilateral Tibial Fractures Nonementioning
confidence: 99%
“…Flap (IIIB) Pro [11] Vascular injury Pro [7] Open injury Pro [2,5] Weightbearing status postoperatively Pro [15,26] Con [35] Fibular fracture fixation Pro [15,38] Con [39,42] …”
Section: Bilateral Tibial Fractures Nonementioning
confidence: 99%
“…This is an important point, also observed by Choudry et al, illustrating that a flap revision or a second flap can often allow limb salvage [20]. At our institution, local muscle flaps are not used for immediate soft tissue cover after lower extremity trauma due to high complication and revision rates [3,18,20].…”
Section: Discussionmentioning
confidence: 78%
“…Choudy et al also found a higher non-union rate and infection rate in patients with flap cover after day seven [20]. Gopal et al and Sinclair et al reported series of open tibial fractures with very early skin cover (before day three) and definitive stabilization; 90-95 % of these patients had successful flap cover, with no infection, union of the fracture and excellent outcome without pain or walking disability [4,5].…”
Section: Discussionmentioning
confidence: 93%
“…[22] 2004 Free tissue transfer + radiotherapy Choudry et al . [23] 2008 Free tissue transfer Saito et al . [24] 2010 Free tissue transfer + bone reconstruction Zweifel-Schlatter et al .…”
Section: Thighmentioning
confidence: 99%
“…In addition to considering the need for adjuvant radiotherapy, the soft tissue of this area is very thin and must provide a smooth surface for the tendons underneath. Traditional flaps used to cover defects of the distal third of the foot have included the rectus abdominis, latissimus dorsi, gracilis, and rectus femoris flaps [23] . Free scapular and ALT flaps have also been used with adequate results [24] .…”
Section: Ankle/footmentioning
confidence: 99%